2011
DOI: 10.1080/09297049.2010.533166
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Test of Memory Malingering (TOMM) among a large clinic-referred pediatric sample

Abstract: Growing concerns with suboptimal effort in pediatric populations have led clinicians to investigate the utility of symptom validity tests (SVT) among children and adolescents. Performance on the Test of Memory Malingering (TOMM) was analyzed among a clinical sample of individuals ranging in age from 5 through 16 years. The 101 patients were referred for a variety of learning, developmental, psychiatric, and neurological concerns. All children were administered the TOMM as part of a clinical neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Recent research has indicated that children as young as 5 years of age can pass the Test of Memory Malingering (TOMM; Tombaugh 1996) at levels at par with adults (Constantinou and McCaffrey 2003;Donders 2005b;Kirk et al 2009). It should be noted that the TOMM is ideal for younger children because it is a picture recognition test and requires no word reading.…”
Section: Special Considerations: Pediatric Effort and Motivationmentioning
confidence: 99%
“…Recent research has indicated that children as young as 5 years of age can pass the Test of Memory Malingering (TOMM; Tombaugh 1996) at levels at par with adults (Constantinou and McCaffrey 2003;Donders 2005b;Kirk et al 2009). It should be noted that the TOMM is ideal for younger children because it is a picture recognition test and requires no word reading.…”
Section: Special Considerations: Pediatric Effort and Motivationmentioning
confidence: 99%
“…Nonetheless, PVTs are essential in the interpretation of neuropsychological test data so as to understand whether participants are providing sufficient effort during testing (Sharland and Gfeller, 2007;McCarter et al, 2009;Fox, 2011). PVTs have also been increasingly used for the assessment of effort in nonlitigation settings, including in children, adolescents, healthy university students, and in neurological disorders (Merten et al, 2007;Locke et al, 2008;Axelrod and Schutte, 2011;Kirk et al, 2011;Brooks et al, 2012;Wisdom et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The practice of using the TOMM in pediatric samples has largely maintained the same adult published cut-off scores on Trial 2 or Retention in order to determine whether the results suggest non-credible performance (Tombaugh, 1996). As with adults, the Retention trial is used only if the child does not pass Trial 2, although in many studies, the Retention is administered regardless of Trial 2 performance to clarify performance patterns across the trials (Blaskewitz, Merten, & Kathmann, 2008; Kirk, et al, 2011; Loughan & Perna, 2014; Rienstra, Spaan, & Schmand, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In a mixed clinical sample of children ages 5–16 years (approximately half of whom were diagnosed with ADHD), Kirk et al (2011) reported that 96% of the participants earned an acceptable score on TOMM Trial 2 and Retention, and none of those with ADHD were among the 4% with non-credible performance. Similarly, Loughran and Perna (2014) reported that 93% of the children with ADHD in their sample achieved an acceptable score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation